A framework for conceptualizing impact assessment and promoting impact culture in agricultural research - Alene, Arega D.; Manyong, Victor M.; Gockowski, J.; Coulibaly, O.; Abele, S. (2006)
Assessing the impact of agricultural research can assist with setting priorities, providing feedback to the research programs, and demonstrating actual benefits of the products of agricultural research. Towards this end, many national and international agricultural research centers have institutionalized impact assessment. However, a number of conceptual and operational difficulties remain that limit the scope and depth of impact assessment work. The objective of this document is to develop a framework for conceptualizing and promoting impact assessment in agricultural research. First, the linkages between agricultural research and rural livelihoods and the implications for evaluating the impact of agricultural technologies are illustrated, using the sustainablerural livelihood framework. Secondly, a strategy for institutionalizing anappropriate data system is proposed to make impact assessment an integral part of the agricultural research process. To operationalize the data system, data sheets for each stage of the impact assessment process are developed to guide researchers in gathering relevant and adequate information relating to each agricultural technology. Implementation of data systems requires biophysical and social scientists to work jointly towards generating and maintaining data for impact assessment.